Peace Agreement on Maslahah in Distribution of Inheritance in Sasak Tribe’s Muslim Community - Syafi’i, Muhammad; Abdullah, Abdullah; Muslihun, Muslihun; Mutawali, Mutawali; Jamaludin, Husna (Jurnal Hukum Islam, 2025)
In Indonesia, conflicts pertaining to in the division of inheritance among Muslim communities often occur, resulting in family discord. This study examines the implementation and impact of suluh—a peace agreement based on mutual understanding—in resolving conflicts over the division of inheritance. This study was conducted in the Sasak tribe’s Muslim community using qualitative methods and approaches. Results show that suluh in the Sasak tribe’s Muslim community is performed when the testator is alive and when they die. When alive, the distribution of inheritance is based on the principle of need and service in managing the inheritance. Meanwhile, when dead, it is divided equally among male and female heirs based on a certain replacement agreement (takharuj or taṣaluh)—giving all or some assets to one or several heirs and payment of the inheritance price by the other heirs. Suluh has an impact on family harmony and the welfare of economically disadvantaged heirs because of unequal distribution of shares among siblings. Reportedly, female heirs, considering maslahah, voluntarily accepted the distribution of inheritance to maintain harmony and family integrity. This study can serve as a reference for the global Muslim community, which faces the same problems in inheritance law practices that intersect with local culture.